1975
DOI: 10.1128/aac.7.6.811
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic G-418, a New Micromonospora-Produced Aminoglycoside with Activity Against Protozoa and Helminths: Antiparasitic Activity

Abstract: Antibiotic G-418 was shown to be superior to paromomycin and metronidazole in cecal amoebiasis. Of particular interest was the high degree of activity seen with a relatively short treatment at low levels. Although the antibiotic was trichomonacidal in vitro at low levels, in vivo results indicated that at levels tested the antibiotic did not always affect cures. The antibiotic appears to have promise as an anticestode agent, being more active than paromomycin against Hymenolepis nana an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Recent studies, demonstrating the potential of some AGs to influence translational processes of eukaryotes, highlighted these compounds as potential therapeutic candidates for the treatment of a wide variety of parasite related infections (8)(9)(10)(11)(12) and some genetic disorders caused by nonsense mutations (5-7). However, despite these promising clinical results, the mechanistic and structural information regarding AGs action in eukaryotes is currently very limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies, demonstrating the potential of some AGs to influence translational processes of eukaryotes, highlighted these compounds as potential therapeutic candidates for the treatment of a wide variety of parasite related infections (8)(9)(10)(11)(12) and some genetic disorders caused by nonsense mutations (5-7). However, despite these promising clinical results, the mechanistic and structural information regarding AGs action in eukaryotes is currently very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Such works highlighted the potential of some AGs for treating nonsense mediated human genetic disorders by encoding near-cognate tRNA molecules at premature termination codon positions (5)(6)(7). Other studies have shown that specific AGs can be used as alternative treatments for infections caused by human parasitic protozoa such as trypanosomiasis, giardiasis, amoebiasis and leishmaniasis (8)(9)(10)(11)(12). Nevertheless, despite the great potential use of AGs for additional therapeutic purposes, very little information is available regarding their molecular mechanisms of action in eukaryotes.…”
mentioning
confidence: 99%
“…Whereas all clinically used aminoglycosides are inhibitors of prokaryotic protein synthesis at commonly accepted therapeutic concentrations (Յ25 g/ml), they may also affect the protein synthesis of mammalian cells at larger concentrations (96), probably through nonspecific binding to eukaryotic ribosomes and/or nucleic acids. Molecules with a hydroxyl function at C-6Ј in place of an amino function, such as in kanamycin C, gentamicin A factors, and antibiotic G418 (3Ј,4Ј-dihydroxy-6Јhydroxy-6Ј-deamino-gentamicin C 1 , also called geneticin [30]), are more effective inhibitors of eukaryotic protein synthesis (22,52). Geneticin and hygromycin B (an atypical aminoglycoside with properties similar to G418) are now commonly used in molecular biology to select eukaryotic cells transfected with a gene coding for an appropriate aminoglycoside-modifying enzyme (17,88).…”
Section: Basis Of Antimicrobial Actionmentioning
confidence: 99%
“…Of those which do, many belong to the aminoglycoside family of antibiotics. Hygromycin B (6,10) and antibiotic G-418 (11) are active against both nematodes and cestodes. The destomycins (12,16) are active only against nematodes, whereas paromomycin (22) and antibiotic complex S15-1 (1) are cestocidal.…”
mentioning
confidence: 99%